In and of the Mediterranean : medieval and early modern Iberian studies - Hamilton, Michelle, 1969-; Silleras-Fernandez, Nuria (Hispanic issues (Vanderbilt University), 2015)
"The Iberian Peninsula has always been an integral part of the Mediterranean world, from the age of Tartessos and the Phoenicians to our own era and the Union for the Mediterranean. The cutting-edge essays in this volume examine what it means for medieval and early modern Iberia and its people to be considered as part of the Mediterranean"--